The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1075547014555997
|View full text |Cite
|
Sign up to set email alerts
|

Putting Environmental Infographics Center Stage

Abstract: Infographics, which integrate visuals and text, can increase audience engagement with message content. Relying on two experiments, this study demonstrates the role of visuals for decisions to critically evaluate pro-environmental messages. Using the Elaboration Likelihood Model as a theoretical foundation, we demonstrate that individuals engage in greater levels of issue-relevant thinking when shown infographics compared to messages that rely just on text or just on illustration, with learning preferences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(59 citation statements)
references
References 48 publications
3
54
0
2
Order By: Relevance
“…Given that both iterations summarized the same study, the GI iteration's higher score lends support to Lazard and Atkinson's (2015) assertions that the "how" may be as influential as the "what" being presented. Additionally, the participants' indication that they were more likely to read the GI document after their relatively quick evaluations bolsters the notion that the hedonic qualities afforded by first impressions may influence their choice to read the information.…”
Section: Journal Of Interior Design 27mentioning
confidence: 64%
See 3 more Smart Citations
“…Given that both iterations summarized the same study, the GI iteration's higher score lends support to Lazard and Atkinson's (2015) assertions that the "how" may be as influential as the "what" being presented. Additionally, the participants' indication that they were more likely to read the GI document after their relatively quick evaluations bolsters the notion that the hedonic qualities afforded by first impressions may influence their choice to read the information.…”
Section: Journal Of Interior Design 27mentioning
confidence: 64%
“…Smaller text is considered less important; thus, larger text is often read first. Additionally, Lazard and Atkinson (2015) found that integrative visuals (i.e., those relying on both images and text) were more engaging than messages relying singularly on text or illustrations alone. In their study, participants had more volume and vividness of thought as well as sensitivity to integrative visual message, leading them to conclude that in addition to being popular, infographics can also be very effective, guiding viewers through complex information.…”
Section: Text and Imagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Historically and traditionally, ELM research has used text-based messages as the persuasive communication component and any visual components have been seen as peripheral cues (Lazard & Atkinson, 2015). However, "mediated messages are perceived holistically; that is, all visual elements of a message-both imagery and text-are seen as one constructed unit on first impression or initial glance" (Lazard & Atkinson, 2015, p. 10).…”
Section: Introductionmentioning
confidence: 99%